Individual differences in stop‐related activity are inflated by the adaptive algorithm in the stop signal task. Issue 8 (15th April 2018) - D'Alberto, Nicholas; Chaarani, Bader; Orr, Catherine A.; Spechler, Philip A.; Albaugh, Matthew D.; Allgaier, Nicholas; Wonnell, Alexander; Banaschewski, Tobias; Bokde, Arun L.W.; Bromberg, Uli; Büchel, Christian; Quinlan, Erin Burke; et al.
Abstract: Research using the Stop Signal Task employing an adaptive algorithm to accommodate individual differences often report inferior performance on the task in individuals with ADHD, OCD, and substance use disorders compared to non‐clinical controls. Furthermore, individuals with deficits in inhibitory control tend to show reduced neural activity in key inhibitory regions during successful stopping. However, the adaptive algorithm systematically introduces performance‐related differences in objective task difficulty that may influence the estimation of individual differences in stop‐related neural activity. This report examines the effect that these algorithm‐related differences have on the measurement of neural activity during the stop signal task. We compared two groups of subjects (n = 210) who differed in inhibitory ability using both a standard fMRI analysis and an analysis that resampled trials to remove the objective task difficulty confound. The results show that objective task difficulty influences the magnitude of between‐group differences and that controlling for difficulty attenuates stop‐related activity differences between superior and poor inhibitors. Specifically, group differences in the right inferior frontal gyrus, right middle occipital gyrus, and left inferior frontal gyrus are diminished when differences in objective task difficulty are controlled for. Also, when objective task difficulty effects are exaggerated, group differences in stop related activity emerge in other regions of the stopping network. The implications of these effects for how we interpret individual differences in activity levels are discussed.